Evaluation of Implementing the 4A Concept in Unique Tourist Destinations at Tawun Tourist Park, Ngawi - Rahmatin, Leily Suci; Suksmawati, Herlina; Nuryananda, Praja Firdaus (Future Science, 2023)
Tawun Tourism Park, located in Ngawi, is a special interest tourist destination which is a leading tourist attraction. Not only local tourists in Ngawi who visit this place, but also tourists who come from outside the city are very enthusiastic to see the excitement of the Tawun Tourism Park. With the improvement of the management superstructure of the Tawun Tourism Park and support from the local government, the research team assessed the need for scientific support for tourism analysis. This support can be formed through a readiness analysis and the application of the 4A concept at the Tawun Tourism Park. This article will discuss the extent to which awareness of good tourism management has been used by the Tawun Tourism Park management and a description of the implementation of the 4A concept in that place so far. To write this article, one research was carried out in three stages, namely the preparation stage, the field study implementation stage and the evaluation stage. The research used a descriptive-qualitative type of research and data collection techniques were carried out by interviews and observations. The results of the research conducted are the facts in the field that Tawun Tourism Park has met the basic criteria for tourism, namely A4 (attraction, amenity, accessibility, ancillary) and the majority of residents involved in Tawun Tourism Park tourism are local residents, so this is in line with the spirit of development a tourist destination.